Matemática financeira: discussão de resultados e proposta para capacitação de professores - Garcia, Solano Martinazzi (2014)
This work starts from the analysis of a discursive issue of UFES’s entrance exam for freshmen in 2013, involving Financial Mathematics knowledge, in which the candidates had a low rate of right answers. To determine the possible causes for the low performance the teaching materials analysis was first, with that it was verified that the deficiencies were not of the same reasons that could cause such results to be achieved. After researching and testing it was found that mathematics teachers, were mostly not trained to teach Financial Mathematics in High School. From this finding, the focus of this work became the development of a proposal for the training the teachers in teaching Financial Mathematics at High School and also suggesting changes in textbooks, about teaching certain content (mainly simple interest ), including some topics that are not being addressed and deepening in others, introduction of the method of Arrows to the equivalence of values in time, Systems amortization payments and the use of computer programs. This work aims to contribute to the improvement in teaching Financial Mathematics besides being a support for teachers who will be able to use it as background material for their classes.